2014
DOI: 10.1007/s00265-014-1776-x
|View full text |Cite
|
Sign up to set email alerts
|

What drives flexibility in primate social organization?

Abstract: The importance of behavioral flexibility for understanding primate ecology and evolutionary diversity is becoming increasingly apparent, and yet despite the abundance of long-term studies across diverse sampling localities, we still do not understand the myriad factors responsible for amongsite variation in species' social organization. The goals of our study were to address this question via three main objectives: to quantify social organization flexibility (i.e., across-site intraspecific variation) of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 90 publications
(88 reference statements)
0
26
0
1
Order By: Relevance
“…Furthermore, male–male competition for access to females, both within and between groups, may limit or favor the formation of multimale groups . In addition to interspecies differences in social organization, socioecological theory has also been used to explain variation within species . In particular, there are species in all primate taxa that vary in the proportion of social groups that are one‐male and multimale (e.g., Verreaux's sifaka, Phayre's leaf monkeys, hamadryas baboons, ursine colobus monkeys, hanuman langurs, black howler monkeys, and mountain gorillas).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, male–male competition for access to females, both within and between groups, may limit or favor the formation of multimale groups . In addition to interspecies differences in social organization, socioecological theory has also been used to explain variation within species . In particular, there are species in all primate taxa that vary in the proportion of social groups that are one‐male and multimale (e.g., Verreaux's sifaka, Phayre's leaf monkeys, hamadryas baboons, ursine colobus monkeys, hanuman langurs, black howler monkeys, and mountain gorillas).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition to interspecies differences in social organization, socioecological theory has also been used to explain variation within species. [10][11][12][13] In particular, there are species in all primate taxa that vary in the proportion of social groups that are one-male and multimale (e.g., Verreaux's sifaka, 14 Phayre's leaf monkeys, 15 hamadryas baboons, 16 ursine colobus monkeys, 17 hanuman langurs, 18 black howler monkeys, 19 and mountain gorillas 20 ). In a critical review of primate socioecology, Clutton-Brock and Janson 21 recommend that to understand variability in within-species and between-species grouping patterns researchers should consider how feeding competition and predation interact with variation in reproductive strategies and life history parameters of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Residuals from both nonphylogenetic linear [Sol and Price, 2008;Weisbecker and Goswami, 2010;Sol et al, 2012;Castillo-Morales et al, 2014] and reduced major axis regressions (RMA) [Shultz and Dunbar, 2006], and phylogenetically corrected RMA [Kamilar and Baden, 2014] or PGLS [Pérez-Barbería et al, 2007;Swanson et al, 2012;Smaers and Soligo, 2013;Symonds et al, 2014], have been used to obtain relative brain size, although phylogenetically corrected methods should always be used (see below; also see Hansen and Bartoszek [2012] for arguments against using RMA regressions in this context). However, several studies have shown that obtaining the residuals from a linear regression to remove the effect of one variable and perform subsequent analysis with these residuals is not appropriate [Darlington and Smulders, 2001;García-Berthou, 2001;Freckleton, 2002].…”
mentioning
confidence: 99%
“…The effect of ignoring intraspecific variation in comparative analyses has been studied for only a few systems, predominantly relying on simulated rather than actual data (Harmon and Losos, 2005; Ives et al, 2007; Felsenstein, 2008; Hansen and Bartoszek, 2012). Researchers have only recently begun to assess intraspecific variation in a comparative context (e.g., Kamilar and Baden, 2014; Pap et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In chimpanzees, for example, communities range in size from approximately 20 to 200 individuals (e.g., Wilson et al, 2014), yet in one widely cited paper analyzing the relationship between neocortex size and group size, this variability is collapsed into a single value, 53.5 (Dunbar, 1992). While a species mean may accurately reflect the situation in solitary and socially monogamous primates where the only source of variation in “group” size is due to offspring being born and dispersing at maturity, a species mean is likely to conceal biologically meaningful variation for primates living in larger social groups (Kamilar and Baden, 2014; Patterson et al, 2014). …”
Section: Introductionmentioning
confidence: 99%